Steganography technique using modulus arithmetic - Jaafar, Sayuthi; Manaf, Azizah A.; Zeki, Akram M. (2007)
This new technique will use modulus arithmetic to incorporate secret-information into a host-image. Modulus arithmetic is used as the mechanism for embedding and extracting process. Modulus-m operation indicates l-bits of the secret-information can be incorporated into the host-image pixel. This approach works in a fully spatial domain manner, so one need to deliberately observe the spatial characteristic among the pixel distribution in the host-image and the secret-information. Pixels are represented by a decimal value (0 – 255).